2010
DOI: 10.1029/2009gl041391
|View full text |Cite
|
Sign up to set email alerts
|

Holocene carbon cycle dynamics

Abstract: [1] We are investigating the late Holocene rise in CO 2 by performing four experiments with the climate-carbon-cycle model CLIMBER2-LPJ. Apart from the deep sea sediments, important carbon cycle processes considered are carbon uptake or release by the vegetation, carbon uptake by peatlands, and CO 2 release due to shallow water sedimentation of CaCO 3 . Ice core data of atmospheric CO 2 between 8 ka BP and preindustrial climate can only be reproduced if CO 2 outgassing due to shallow water sedimentation of CaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 33 publications
6
75
0
1
Order By: Relevance
“…To put such high anomalies into perspective to variations potentially observed in the carbon cycle it is useful to consider the human perturbation of the carbon cycle of the recent past. The unprecedented anthropogenic CO 2 emissions from fossil fuel burning and land use, which amount to more than 500 Gt C in the last 250 yr (Boden et al, 2011;Houghton, 2010), has led to a rise of more than 100 ppm in atmospheric CO 2 (Etheridge et al, 1996;Keeling et al, 2009) and a δ 13 C atm decrease of −1.9 ‰ from pre-industrial conditions of −6.3 to −8.2 ‰ in 2010 AD (Francey et al, 1999;Keeling et al, 2010). Thus, a 0.7 ‰ drop in 200 yr during Termination II accompanied by a CO 2 increase of not more than 20 ppm represents an extraordinary perturbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To put such high anomalies into perspective to variations potentially observed in the carbon cycle it is useful to consider the human perturbation of the carbon cycle of the recent past. The unprecedented anthropogenic CO 2 emissions from fossil fuel burning and land use, which amount to more than 500 Gt C in the last 250 yr (Boden et al, 2011;Houghton, 2010), has led to a rise of more than 100 ppm in atmospheric CO 2 (Etheridge et al, 1996;Keeling et al, 2009) and a δ 13 C atm decrease of −1.9 ‰ from pre-industrial conditions of −6.3 to −8.2 ‰ in 2010 AD (Francey et al, 1999;Keeling et al, 2010). Thus, a 0.7 ‰ drop in 200 yr during Termination II accompanied by a CO 2 increase of not more than 20 ppm represents an extraordinary perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…The major δ 13 C atm increases in Fig. 2 starting at around 130 000 and 12 000 yr BP, respectively, can be largely explained by the regrowth of the terrestrial biosphere (Köhler et al, 2005;Elsig et al, 2009;Kleinen et al, 2010;Menviel and Joos, 2011) as well as warming SST, where a SST change of +1 K induces a δ 13 C atm fractionation by about +0.1 ‰ (Zhang et al, 1995). The δ 13 C atm signal induced from terrestrial carbon build-up is a mixture of a signal composed of C4 (δ 13 C ∼ −10 to −14 ‰) and C3 (δ 13 C ∼ −22 to −30 ‰) plant type origin (O'Leary, 1981, Ehleringer et al, 1993.…”
Section: Comparison Of Sequence Of Events Around Termination II and Tmentioning
confidence: 99%
“…On the other hand, Brovkin et al (2002), as well as Menviel and Joos (2012), found almost no effect of SST changes on CO 2 during the Holocene. Kleinen et al (2010), using the CLIMBER2-LPJ model, showed that the trend in atmospheric CO 2 over the Holocene is controlled by the balance of two slow processes: (1) carbon uptake by boreal peatlands, which is (slightly over-) compensated for by (2) the outgassing of CO 2 due to the accumulation of CaCO 3 in shallow oceanic areas. Finally, Menviel and Joos (2012) investigated the Holocene CO 2 rise by applying the Bern3D ocean carbon cycle model, with prescribed scenarios of shallow-water carbonate accumulation and land C uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the total terrestrial C balance, derived from the measured parallel evolution of atmospheric CO 2 and its isotopic signature (δ 13 C), suggests a small reduction of only 36 ± 37 PgC since 5 kyBP (10). Further, an ocean C-cycle modeling study (11) shows that the Holocene (since 11.7 kyBP) CO 2 and δ 13 C evolutions are quantitatively explained by the combination of the reconstructed terrestrial C balance (10) and ocean C-cycle changes after the Last Glacial Maximum (LGM) with delayed effects during the Holocene, associated with terrestrial carbon changes and the carbonate compensation mechanism (4, 11, 12), sea level rise, and coral reef buildup (13,14).However, two factors have rendered previous analyses of the terrestrial carbon budget and the quantification of its individual components inconclusive. First, differing assumptions regarding the per-capita land requirement for the back projection of Significance Timing, extent, and impacts of preindustrial agricultural expansion are uncertain, yet crucial for understanding the role of humans in the Earth's environmental history.…”
mentioning
confidence: 99%
“…In addition, the total terrestrial C balance, derived from the measured parallel evolution of atmospheric CO 2 and its isotopic signature (δ 13 C), suggests a small reduction of only 36 ± 37 PgC since 5 kyBP (10). Further, an ocean C-cycle modeling study (11) shows that the Holocene (since 11.7 kyBP) CO 2 and δ 13 C evolutions are quantitatively explained by the combination of the reconstructed terrestrial C balance (10) and ocean C-cycle changes after the Last Glacial Maximum (LGM) with delayed effects during the Holocene, associated with terrestrial carbon changes and the carbonate compensation mechanism (4, 11, 12), sea level rise, and coral reef buildup (13,14).…”
mentioning
confidence: 99%